Medium term follow-up after percutaneous pulmonary valve replacement with the Melody® valve - Cools, Bjorn; Budts, Werner; Heying, Ruth; Boshoff, Derize; Eyskens, Benedicte; Frerich, Stefan; Troost, Els; Gewillig, Marc (International journal of cardiology. Heart & vasculature, 2015)
Data on long term function of the Melody valve are scarce. Patients and methods: single institution; results of percutaneous pulmonary valve implantation (PPVI) from 2006 to 2014. The function of the valved conduit was analyzed by Doppler echocardiography. Annual Chest X-ray after implant and permanent screening for events (e.g. Endocarditis). 112 Melody valves were implanted in 111 patients; mean age 19.3years (4.5–81.6). No pre-stenting of the RVOT was performed (n=4) at first. In the next 107 patients pre-stenting was always performed. In 82 patients 1 pre-stent, 18 patients 2, in 6 patients 3 stents and 1 patient 4 stents were used. The Melody stent was dilated up to 24mm (n=4), 22mm (n=72), 20mm (n=28) and 18mm (n=6). When stenotic, the Doppler gradient reduced from 67.0mmHg (SD 13.9) to 18.9mmHg (SD 10.4) (p<0.001); pulmonary regurgitation (PR) was reduced from median 3.5/4 (range 0–4/4) to none or trivial (p<0.001). There was no significant change in RVOT peak velocity at 5years (p=0.122) nor PR (p=0.835). Type 1 stent fractures were observed in 1/4 non-pre-stented patients and in 5/107 pre-stented (p<0.05). Endocarditis occurred in 8/112 valves; freedom of endocarditis was 85% at 5years. In 2 patients early surgical replacement was necessary. Six were sterilized with antibiotic treatment; 2 patients required re-stenting and re-PPVI due to residual gradient. Adequate pre-stenting of the RVOT before PPVI nearly abolishes or delays stent fracture. Cusp function is well preserved in mid-term follow-up; endocarditis is a threat.